Analisis Sistem Akuntansi Pembelian Barang Dagangan (Studi Kasus Pada Rafamart Rantauprapat Labuhanbatu) - Fitriadany, Eno; Siregar, Saparuddin; Syafina, Laylan (Universitas Labuhanbatu, 2023)
This study aims to determine how the accounting system of merchandise purchases in Rafamart RantauprapatLabuhanbatu, and to determine the results of the recording and valuation of merchandise using the FIFO method (First In First Out) with a perpetual system based on Computerization and manual using books. The type of data used in this study is the primary data in the form of interviews and secondary in the form of purchase and sales invoices at Rafamart Rantauprapat Labuhanbatu. Data collection techniques used in this study are interview techniques and documentation techniques. Data analysis techniques used are descriptive techniques that is how to analyze, interpret, and process data on the purchase of merchandise in Rafamart Rantauprapat Labuhanbatu. The results of this study indicate that Rafamart Rantauprapat Labuhanbatu has implemented a trading goods purchase accounting system that assists companies in conducting daily records using books manually and also computerized. In the system of recording the accounting of merchandise purchases using a Prepetual system, where the recording of purchases and sales are recorded using books. The method of recording and assessing purchases for merchandise inventories using the FIFO (First In First Out) Method, and Rafamart Rantauprapat Labuhanbatu is in accordance with PSAK (statement of Financial Accounting Standards) number 14 regarding purchases and inventories of merchandise. Â